2013
DOI: 10.1038/srep01706
|View full text |Cite
|
Sign up to set email alerts
|

The utility of Plasmodium berghei as a rodent model for anti-merozoite malaria vaccine assessment

Abstract: Rodent malaria species Plasmodium yoelii and P. chabaudi have been widely used to validate vaccine approaches targeting blood-stage merozoite antigens. However, increasing data suggest the P. berghei rodent malaria may be able to circumvent vaccine-induced anti-merozoite responses. Here we confirm a failure to protect against P. berghei, despite successful antibody induction against leading merozoite antigens using protein-in-adjuvant or viral vectored vaccine delivery. No subunit vaccine approach showed effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 75 publications
(161 reference statements)
1
32
0
Order By: Relevance
“…In vivo detection of P. berghei infection on BALB/c mice. We used the murine malaria parasite P. berghei, which is a good model of human P. falciparum infection, for the in vivo validation of this approach 21 . We intraperitoneally infected BALB/c mice (n = 25) with 10 4 P. berghei parasites (denoted as Day 0) (Methods and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo detection of P. berghei infection on BALB/c mice. We used the murine malaria parasite P. berghei, which is a good model of human P. falciparum infection, for the in vivo validation of this approach 21 . We intraperitoneally infected BALB/c mice (n = 25) with 10 4 P. berghei parasites (denoted as Day 0) (Methods and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Pb/Pf M19 chimeric strain was also used to challenge BALB/c mice receiving passive transfer of rabbit anti-Pf MSP1 42 IgG, with complete sterile protection observed (35). In two other studies, passive transfer of rabbit anti-Pf MSP1 19 or immunizations with formulations based on the Pf MSP1 19 sequence did not protect BALB/c or C57BL/6 mice from challenge with Pb/Pf M19 (36,37). These disparities may be due to the use of different antigens and formulations for the mouse vaccinations and for raising rabbit antibodies for passive transfers, as well as for differences in mice colonies that may alter the kinetics of mouse infections with P. berghei.…”
Section: Discussionmentioning
confidence: 99%
“…Humoral responses have been shown to play an indispensable role in protection against malaria by blocking merozoite invasion and neutralizing pRBCs for macrophage phagocytosis [ 24 , 25 ]. However, subunit vaccine failure against P. berghei erythrocyte-stage parasite challenge has often been observed [ 26 , 27 ], with only a few trials showing some degree of protection in mouse model [ 22 , 28 ]. The difficulties in achieving protection against P. berghei might be caused by suppression or evasion of the immune system during the infection.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties in achieving protection against P. berghei might be caused by suppression or evasion of the immune system during the infection. In fact, alongside the sequestration of parasites in blood capillaries, erythrocytic-stage P. berghei can rapidly suppress MHC class I and class II presentation of malarial antigens by APCs, thereby preventing the development of protective immunity in vaccinated mice [ 27 , 29 ]. A recent study has shown that vaccination of mice with recombinant P. berghei schizont egress antigen-1 (PbSEA-1) significantly reduces parasitemia and delays mortality.…”
Section: Discussionmentioning
confidence: 99%